Promising neuroprotective potential of naringenin against trimethyltin-induced cognitive deficits and hippocampal neurodegeneration in rats - Faryadras, Kimia; Golchoobian, Ravieh; Iranzadeh, Saeid; Roghani, Mehrdad (Frontiers in Neuroscience, 2025)
IntroductionLearning and memory deficits are clinical characteristics of Alzheimer’s disease (AD), often leading to diminished functionality. The neurotoxicant trimethyltin (TMT) is a valuable research tool for inducing cognitive impairment and hippocampal neurodegeneration and studying AD pathogenesis and treatment. Naringenin is a flavonoid with potential neuroprotective effects. This study sought to investigate the neuroprotective potential of naringenin against hippocampal neurodegeneration induced by TMT neurotoxicity and identify some underlying molecular mechanisms.MethodsNeurodegeneration was induced through an 8 mg/kg intraperitoneal injection of TMT, followed by oral administration of naringenin (25 and 100 mg/kg) for 21 days. Behavioral assessments, including novel object discrimination (NOD), Y-maze, and passive avoidance tests, were carried out to evaluate cognitive functions. Biochemical assays for oxidative/nitrosative stress, mitochondrial membrane potential (MMP), inflammation, and acetylcholinesterase (AChE) enzyme activity, as well as AD pathology-specific markers, were conducted. To further validate the results, histological assessments of the CA1 hippocampal region using Nissl staining and immunohistochemical identification of 3-nitrotyrosine (3-NT) were performed.Results and discussionNaringenin exhibited a dose-dependent inhibition of CA1 neuronal loss and reversed TMT-induced cognitive deficits. It markedly decreased hippocampal levels of malondialdehyde (MDA), nitrite, tumor necrosis factor-alpha (TNFα), and AChE activity while enhancing catalase and superoxide dismutase (SOD) activities, 3-nitrotyrosine (3-NT) immunoreactivity, and MMP. Furthermore, findings demonstrated that naringenin mitigated the TMT-induced elevation in hippocampal levels of AD-specific proteins, including phosphorylated tau (p-tau), amyloid-beta (Aβ), and presenilin 1. Naringenin may be postulated as a promising therapeutic candidate for AD and related neurodegenerative conditions by mitigating oxidative and nitrosative stress, maintaining mitochondrial integrity, decreasing inflammation, and modulating pathways of neurodegeneration.